RANCANG BANGUN APLIKASI ABSENSI PEGAWAI PADA DINAS PERHUBUNGAN KOTA PRABUMULIH BERBASIS WEB - Kharisma Nisa; Ariansyah; Ahmad Barnianto (Elkom: Jurnal Elektronika dan Komputer, 2023)
This study aims to design and build an employee attendance management application. At the Prabumulih City Transportation Service, this application is designed to simplify the process of making employee data reports. At the Prabumulih City Transportation Service, the method carried out at the Transportation Service still uses the manual method, which is still using paper, then if the submission is approved by the staff, the admin will directly input it into Microsoft Excel. Which often results in problems such as, time leaks. The problems that exist in the Department of Transportation are as follows attendance, the process of recording attendance and reporting as a result it will take time to recap and make reports, and how to design and build an employee attendance application at the Department of Transportation of the City of Prabumulih. Therefore the authors designed a Web-Based Application at the Transportation Service Titled "Design of Employee Attendance Applications at the Web-Based Prabumulih City Transportation Service".